Network organizations: The structural arrangement behind new organizational forms - José L. Alvarez; M. Anton Ferreira (South African Journal of Business Management, 1995)
This article elaborates the main meanings of the concept 'network organization' and the underlying structural arrangement behind most of the new organizational forms and the main alternative to the still dominant bureaucratic organizational structure. The concept is applied to four levels of analysis: macro economic and business systems; inter-organizational collaborative arrangements; intra-organizational structures; and informal intra-organizational social systems. Through this taxonomy, an attempt is made to disentangle the different meanings of the concept 'network organization'. Throughout, we seek to highlight the main variables that managers should take into account when making decisions and conducting operations in networks. The article commences with a brief historical overview of the evolution of organizational forms and the driving forces behind current development in the field.
Keywords: 650